Biological activity of microalgae in dermatophytes: Review (Research, Society and Development, 2022)
Microalgae are considered a rich source of biologically active metabolites with potential pharmacological use. In the pharmaceutical industry, microalgae extracts are found to present important biological activities, such as antifungal. Dermatophytosis are cutaneous mycoses caused by fungi called dermatophytes, microorganisms that have a special biotropism for keratinized tissues. The aim of this work was to conduct a literature review on the biological activity of microalgae extracts and compounds in dermatophyte fungi. This is a narrative review of the literature, carried out in the databases PubMed, LILACS, SciELO and Google Scholar. After search, eighteen articles published between 1960 and 2021, in English and French, were selected. Four groups of microalgae have already been explored for their antifungal activity: chlorophytes, diatoms, dinoflagellates and cyanobacteria, totaling 40 species of microalgae already tested in 19 species of dermatophytes. Diatoms and cyanobacteria have the largest number of tests performed against dermatophytes. The most tested species of dermatophytes are T. rubrum and T. menthagrophytes. The extracts of S. platensis, C. Braunii, T. nodosa and T. tenuis and the compounds isolated from the dinoflagellates Goniodoma sp., G. toxicus and Amphidinium sp. have the greatest inhibitory activity. The lack of standardization of tests and the antifungal activity of microalgae extracts already registered for dermatophytes encourages the carrying out of new studies to contemplate the great biodiversity and test the synergistic effect with commercial antifungals.